Hungary and the Soviet Definition of Aggression - Héderváry, Claire de (1956)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): International Commission of Jurists - the Hague The commission's conclusion is that the Soviet Government committed and continues to commit a clear act of aggression against the Hungarian Government according to its own definition of aggression.